Analisis Gaya Bahasa Perbandingan dalam Novel "Jika Kita Tak Pernah Jadi Apa-Apa" Karya Alvi Syahrin. - Yuniarti, Yuniarti; Azis, Azis; Hajrah, Hajrah (Nuances of Indonesian Language, 2025)
This research aims to describe the types and meanings of comparative language styles contained in the novel If We Never Become Nothing by Alvi Syahrin. This research uses descriptive qualitative methods. The data is in the form of sentence quotes related to the use of language styles originating from novels. Data analysis techniques include data reduction, data presentation, and data verification, with data collection techniques namely reading, listening, and note-taking techniques with the researcher himself as the instrument. Meanwhile, the data validity technique uses theoretical triangulation techniques. Based on the results of this research, 4 types of comparative language styles were obtained in the novel If We Never Become Anything by Alvi Syahrin, which includes 18 comparative language styles of similes, 5 metaphors, 15 personifications, and 2 antithesis. data. The four types of comparative language styles are characterized by the use of comparative words (like, as, and as), figurative words, and words that contain two different ideas but are in the same sentence. Markers in this language style aim to provide a beautiful effect that can attract the interest of readers and provide an indirect message by using smoother and more beautiful language.Â